Optimizing lattice Boltzmann simulations for unsteady flows - Artoli, A. M. (2013)
We present detailed analysis of a lattice Boltzmann approach to model time-dependent Newtonian flows. The aim of this study is to find optimized simulation parameters for a desired accuracy with minimal computational time. Simulation parameters for fixed Reynolds and Womersley numbers are studied. We investigate influences from the Mach number and different boundary conditions on the accuracy and performance of the method and suggest ways to enhance the convergence behavior.